Kegiatan Ice Breaking Dalam Meningkatkan Fokus Belajar Anak Usia Dini - ., Nadila Adiansa; ., Retno Wulandari; ., Fahmi (CV. ITTC INDONESIA, 2023)
The study aims to illustrate how important ice breaking activities are in a teaching and learning process. A teacher is not only skilled in delivering learning material, but also must be able to cope when students feel bored with ice breaking activities. In this study using the literature review research method which obtains data or information from relevant previous research such as from journals, books and others, which is then managed and analyzed. The results of this research based on information and data from various journals and books show that ice breaking activities can overcome boredom and loss of focus in early childhood during the learning process. The conclusion of this study with ice breaking activities will help teachers to arouse children's passion in learning and help children to refocus when learning.